Tempeh and Carrots in A Brownies: Their Effects on Nutritional Status of Undernourished Students - Syahrir, Sukfitrianty; Aini, Hurul (Al-Sihah: The Public Health Science Journal, 2022)
The role of nutrition is certainly needed to fulfill the growth process in school-age children because they are still in the growth phase. Whilst optimal growth and development depend on the provision of nutrients, both in terms of quality and quantity, that are considerably right. This study aimed to determine the effects of giving carrots and tempeh as the ingredients of brownies on the nutritional status of undernourished students at elementary school, Gowa Regency. This research was conducted through a quasi-experimental study with a non-randomized control group pretest-posttest design. The number of samples was as many as 24 people, with a sampling technique using purposive sampling. The method of analysis was a paired t-test. The results of this study indicated that there was an effect on nutritional status in the case group (p=0.001) and the control group (0.030,) and there was an effect on body weight in the case group (p=0.001) and the control group (p=0.028). However, providing tempeh brownies as a substitute for carrots and tempeh, brownies had not been able to change the nutritional status of undernourished students for 30 days which was indicated by the average z-score, which was still at <-2 SD. Further research is needed to be developed to determine the duration and efficient frequency of providing intervention in order to get optimal results. This study is expected to provide a new effort in presenting a combination of nutritious foods in an effort to overcome nutritional disorders among children.